THE TRANSFORMATION OF FERGANA VALLEY CITIES: SOCIO-POLITICAL AND ECONOMIC CHANGES (1926-1945) - Abdurakhmonov Adkhamjon (Western European Studies, 2024)
The period between 1926 and 1945 was transformative for the cities in Uzbekistan’s Fergana Valley, as Soviet policies fundamentally altered the region’s social structure, economy, and urban landscape. This paper investigates these changes, focusing on cities like Fergana, Namangan, and Andijan. The study draws on Soviet urban policy analysis, economic shifts due to forced collectivization and industrialization, and the impacts of World War II on local urban life. The findings reveal significant changes that contributed to the modernization of the region within the Soviet socio-political framework, with implications that would resonate in the Valley’s post-war period.
Keywords: Fergana Valley; Soviet Union; urban history; industrialization